Trends in Periprosthetic Knee Infection and Associated Costs: A Population-Based Study Using National Data - Brochin, Robert; Poeran, Jashvant; Vig, Khushdeep S.; Keswani, Aakash; Zubizarreta, Nicole; Galatz, Leesa M.; Moucha, Calin (The Journal of Knee Surgery, 2020)
Given increasing demand for primary knee arthroplasties, revision surgery is also expected to increase, with periprosthetic joint infection (PJI) a main driver of costs. Recent data on national trends is lacking. We aimed to assess trends in PJI in total knee arthroplasty revisions and hospitalization costs. From the National Inpatient Sample (2003–2016), we extracted data on total knee arthroplasty revisions (n = 782,449). We assessed trends in PJI prevalence and (inflation-adjusted) hospitalization costs (total as well as per-day costs) for all revisions and stratified by hospital teaching status (rural/urban by teaching status), hospital bed size (≤299, 300–499, and ≥500 beds), and hospital region (Northeast, Midwest, South, and West). The Cochran–Armitage trend test (PJI prevalence) and linear regression determined significance of trends. PJI prevalence overall was 25.5% (n = 199,818) with a minor increasing trend: 25.3% (n = 7,828) in 2003 to 28.9% (n = 19,275) in 2016; p < 0.0001. Median total hospitalization costs for PJI decreased slightly ($23,247 in 2003–$20,273 in 2016; p < 0.0001) while median per-day costs slightly increased ($3,452 in 2003–$3,727 in 2016; p < 0.0001), likely as a function of decreasing length of stay. With small differences between hospitals, the lowest and highest PJI prevalences were seen in small (≤299 beds; 22.9%) and urban teaching hospitals (27.3%), respectively. In stratification analyses, an increasing trend in PJI prevalence was particularly seen in larger (≥500 beds) hospitals (24.4% in 2003–30.7% in 2016; p < 0.0001), while a decreasing trend was seen in small-sized hospitals. Overall, PJI in knee arthroplasty revisions appears to be slightly increasing. Moreover, increasing trends in large hospitals and decreasing trends in small-sized hospitals suggest a shift in patients from small to large volume hospitals. Decreasing trends in total costs, alongside increasing trends in per-day costs, suggest a strong impact of length of stay trends and a more efficient approach to PJI over the years (in terms of shorter length of stay).
Keywords: knee arthroplasty; revision; periprosthetic joint infection; trends